De domesticatie van democratie in Nederland. Democratie als strijdbegrip van de negentiende eeuw tot 1945 - Henk te Velde (BMGN: Low Countries Historical Review, 2012)
The Domestication of Democracy in the Netherlands: The Concept of Democracy as a Political Weapon from the Nineteenth Century until 1945   Democracy as we know it is a contested combination of majority rule (as opposed to elite rule) and the rule of law (as opposed to dictatorship). This contribution charts the historical debate about the concept of democracy in the Netherlands. Until the 1880s the word democracy was scarcely used in the Dutch parliament and, if used, usually in the derogatory sense of mob rule. Parliamentarians could ignore it because no large democratic reform movement existed until the neo-Calvinist Abraham Kuyper and Socialists began to advocate democracy as the rule of the common people. They used arguments that today would count as populist. In 1917-1919 general suffrage was introduced. In the interwar period liberals and social democrats used ‘democracy’ to defend the values of parliamentary democracy against National Socialism. After the war a new consensus emerged – democracy was first and foremost the absence of dictatorship. Democracy was stripped of its populist side, it was ‘domesticated’. Today it has become clear that this domestication remains contested.